2011
DOI: 10.1177/0883073810390038
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Calcification in an Early-Onset Progressive Leukoencephalopathy

Abstract: Spinal cord calcifications are an unusual finding in pediatric neurology. We here describe a young child who presented severe psychomotor delay, tetraplegia, deafness, and anemia. Neuroradiological investigations revealed severe leukodystrophy and unusual calcifications in the cerebral white matter and all along the medullary pathways. Common infectious and metabolic diseases were ruled out. A mild reduction in the activity of several respiratory chain complexes was documented on muscle biopsy. Of interest, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 16 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…Activity of the Respiratory Chain Complexes Sub-units are Differentially Affected Defects in the translation of mt-DNA-encoded RC subunits were reported to be correlated with mutations within YARS2 [97, 111], MARS2 [98], and FARS2 [104]. In addition, defects in the activity of those complexes were reported to be correlated with mutations within YARS2 [97, 111], SARS2 [108], RARS2 [92, 101], MARS2 [98], FARS2 [104], EARS2 [89], DARS2[112], and AARS2[110]. However, affected subunits may vary from one case to another.…”
mentioning
confidence: 99%
“…Activity of the Respiratory Chain Complexes Sub-units are Differentially Affected Defects in the translation of mt-DNA-encoded RC subunits were reported to be correlated with mutations within YARS2 [97, 111], MARS2 [98], and FARS2 [104]. In addition, defects in the activity of those complexes were reported to be correlated with mutations within YARS2 [97, 111], SARS2 [108], RARS2 [92, 101], MARS2 [98], FARS2 [104], EARS2 [89], DARS2[112], and AARS2[110]. However, affected subunits may vary from one case to another.…”
mentioning
confidence: 99%
“…We read the article by Kuki et al [2011] on “Progressive Leukoencephalopathy with intracranial calcification, congenital deafness, and developmental deterioration” and we found it very interesting. Recently, we reported a very distinctive patient affected by a calcifying leukoencephalopathy involving spinal cord with a pattern we called “track‐like” calcifications [Orcesi et al, 2011]. Our patient presented with systemic symptoms, notably hypochromic microcytic anemia, a mild proteinuria, and laboratory abnormalities of unclear significance such as increased levels of plasma alanine, low concentration of biopterin in CSF, a mild reduction in the activity of several complexes of the respiratory chain.…”
Section: To the Editormentioning
confidence: 80%
“…PUS1 Riley et al, (10) Sasarman et al (35) X-linked sideroblastic anaemia (XLSA) Anaemia ALAS2 Fontenay et al (12) XLSA with ataxia Anaemia ABCB7 Fontenay et al (12) Leigh-syndrome Anaemia Numerous Nagashima et al (13) LHON Anaemia Several Pott & Wong (15) MELAS Anaemia, thrombocytosis Not reported Finsterer (14) TRMA Megaloblastic anaemia SLC19A2 Fleming, (36) Cazzola & Invernizzi (37) AR-SA Sideroblastic anaemia GLRX5 Fleming, (36) Cazzola & Invernizzi (37) Non-syndromic Anaemia Sideroblastic anaemia SLC25A38 Kannengiesser et al (17) mtDNA depletion Anaemia, thrombopenia, T-cells ↓ POLG1 Reichenbach et al (28) Congenital neutropenia Neutropenia HAX-1 Boztug et al (32) LE, cerebral calcification Anaemia DARS2 Orcesi et al (18) MP, hCMP, SLE Anaemia, thrombopenia CII, IV defect Van Hove et al (25) Haemolytic uremic syndrome Anaemia, thrombopenia CII-defect Micheletti et al (19) Myopathy, lactacidosis Anaemia Not reported Inbal et al (16) AR-SA: autosomal-recessive sideroblastic anaemia; hCMP: hypertrophic cardiomyopathy; LE: leucoencephalopathy; LHON: Leber's hereditary optic neuropathy; MELAS: mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes; MLASA: autosomal recessive mitochondrial myopathy, lactacidosis and sideroblastic anaemia; MP: myopathy; mtDNA: mitochondrial DNA; SLE: stroke-like episode; TRMA: thiamine-responsive megaloblastic anaemia;…”
Section: Syndromicmentioning
confidence: 99%
“…While anaemia was never the sole phenotypic feature of MID in the present study, it was always present among other phenotypic features of MID (Table VII). (18,22,23) In nonsyndromic MIDs, anaemia has been described as a phenotypic feature in patients with leucoencephalopathy and intracerebral calcifications due to a DARS2 mutation. (18) Anaemia, together with thrombopenia, has been reported in a 40-year-old man with a combined complex II and IV defect, who also presented with myopathy, renal insufficiency, hypertrophic cardiomyopathy, a stroke-like episode and lactacidosis.…”
Section: Syndromicmentioning
confidence: 99%
See 1 more Smart Citation